2017
DOI: 10.1002/2016gh000024
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hypoxia on gene expression patterns by the human pathogen, Vibrio vulnificus, and bacterial community composition in a North Carolina estuary

Abstract: Estuarine environments are continuously being shaped by both natural and anthropogenic sources which directly/indirectly influence the organisms that inhabit these important niches on both individual and community levels. Human infections caused by pathogenic Vibrio species are continuing to rise, and factors associated with global climate change have been suggested to be impacting their abundance and geographical range. Along with temperature, hypoxia has also increased dramatically in the last 40 years, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Whole genome sequencing has shown that the stressosome gene cluster is particularly well conserved in clinical V. vulnificus isolates (Biotype 1) and less frequently found in environmental strains (Biotype 2), suggesting that the stressosome may play a role during infection 24 , 26 . Furthermore, the rsbRSTX locus is transcribed during periods of reduced oxygen availability in sea water, showing that the stressosome operon is active in the natural habitat of this pathogen 27 . The rsbRSTX gene cluster is also conserved in other important pathogenic Vibrio species including Vibrio coralliilyticus , causing global coral bleaching 28 , Vibrio nigripulchritudo , an emerging pathogen of farmed shrimp 29 , and Vibrio brasiliensis 30 that was isolated from a marine aquaculture environment 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Whole genome sequencing has shown that the stressosome gene cluster is particularly well conserved in clinical V. vulnificus isolates (Biotype 1) and less frequently found in environmental strains (Biotype 2), suggesting that the stressosome may play a role during infection 24 , 26 . Furthermore, the rsbRSTX locus is transcribed during periods of reduced oxygen availability in sea water, showing that the stressosome operon is active in the natural habitat of this pathogen 27 . The rsbRSTX gene cluster is also conserved in other important pathogenic Vibrio species including Vibrio coralliilyticus , causing global coral bleaching 28 , Vibrio nigripulchritudo , an emerging pathogen of farmed shrimp 29 , and Vibrio brasiliensis 30 that was isolated from a marine aquaculture environment 31 .…”
Section: Introductionmentioning
confidence: 99%
“… V. vulnificus experiences variation in O 2 levels both in the environment and in the human host [27]. Moreover, the V.…”
Section: Resultsmentioning
confidence: 99%
“…Next, growth characterisation of the two strains was performed in LBN at 30°C and 37°C, in aerobic and O 2 -depleted conditions. V. vulnificus experiences variation in O 2 levels both in the environment and in the human host (25). Moreover, the V. brasiliensis stressosome has been shown to bind O 2 in vitro (26).…”
Section: Resultsmentioning
confidence: 99%
“…The first formed by the genes encoding for the three stressosome proteins VvrsbR, VvrsbS, VvrsbT (RsbR, RsbS and RsbT in B. subtilis ) and the phosphatase VvrsbX (RsbX) and the latter encoding for a putative regulatory output of the stressosome, a two-component system (TCS) most likely involved in c-di-GMP hydrolysis (22). This locus has been identified in approximately 50% of the sequenced strains and its expression has been proved both in nature and laboratory conditions (2325). Moreover, the heme-binding globin domain at the N-terminal of VvuR and the biochemical characterisation of these proteins from V. brasiliensis has shown a potential role in surviving or tolerating anaerobic conditions (26).…”
Section: Introductionmentioning
confidence: 99%